Pengaruh Edukasi Anestesi Media Lembar Balik terhadap Kecemasan pada Pre Sectio Caesarea - Nabhani Nabhani; Sulastri Sulastri; Widya Setyorini (Quantum Wellness : Jurnal Ilmu Kesehatan, 2024)
Background: Sectio caesarea surgery often causes psychological problems in patients, namely fear which impacts on anxiety which can cause a decrease in conditions such as disorders of the reproductive organs, namely conditions in the uterus, disturbances in blood flow and the need for oxygenation and even discomfort or pain. Efforts to reduce the level of anxiety in patients who are about to undergo surgery must be handled by the anesthetist during the preoperative phase. The way to overcome this can use non-pharmacological techniques given anesthesia education using flipchart media. Research Objectives: To find out the effect of flipchart media anesthesia education on anxiety in pre-sectio caesarean section in patients with sectio caesarea at Ibnu Sina Hospital, Kab. Gresik. Research Methods: This type of research uses a quasi-experimental method with a pre-post test research design with a control group design. Respondents were given pretest and posttest treatment using the APAIS scale measurement. The sample in this study was 24 respondents in the intervention group and 24 respondents in the control group. The sampling technique used consecutive sampling technique. Data collection was carried out in November - June 2023. Research Results: The results of data collection were processed using the Mann Whitney test. Results The Mann Whitney test yielded p=0.000 (p<0.05), so Ha was accepted. Conclusion: There is a significant effect between preoperative anesthesia education using flipchart media on the anxiety level of patients with pre-sectio caesarea